2015
DOI: 10.1097/tp.0000000000000661
|View full text |Cite
|
Sign up to set email alerts
|

Immunoprotection and Functional Improvement of Allogeneic Islets in Diabetic Mice, Using a Stable Indoleamine 2,3-Dioxygenase Producing Scaffold

Abstract: This study shows that incorporation of islets within our novel matrix that is equipped with stable IDO-expressing fibroblasts prolongs allograft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…This was attributed to several different immune factors, including reduced T-cell infiltration into the graft, a shift from a pro-inflammatory Th1 to an anti-inflammatory Th2 response and impaired T-cell priming, although the IDO1-expressing islets did eventually succumb to host immune attack [295,296]. In an effort to further prolong allogenic islet acceptance, Hosseini-Tabatabaei et al [297] recently developed a stable biomimetic scaffold (to re-establish the extracellular matrix that is lost during islet isolation) housing IDO1-expressing fibroblasts to support islet implantation and survival in mice. This method lengthened the survival of islet allografts 4-fold by enhancing Treg infiltration into the graft itself and the draining lymph nodes [297].…”
Section: Transplantation the Ultimate Goal In Organ Transplantationmentioning
confidence: 97%
See 1 more Smart Citation
“…This was attributed to several different immune factors, including reduced T-cell infiltration into the graft, a shift from a pro-inflammatory Th1 to an anti-inflammatory Th2 response and impaired T-cell priming, although the IDO1-expressing islets did eventually succumb to host immune attack [295,296]. In an effort to further prolong allogenic islet acceptance, Hosseini-Tabatabaei et al [297] recently developed a stable biomimetic scaffold (to re-establish the extracellular matrix that is lost during islet isolation) housing IDO1-expressing fibroblasts to support islet implantation and survival in mice. This method lengthened the survival of islet allografts 4-fold by enhancing Treg infiltration into the graft itself and the draining lymph nodes [297].…”
Section: Transplantation the Ultimate Goal In Organ Transplantationmentioning
confidence: 97%
“…In an effort to further prolong allogenic islet acceptance, Hosseini-Tabatabaei et al [297] recently developed a stable biomimetic scaffold (to re-establish the extracellular matrix that is lost during islet isolation) housing IDO1-expressing fibroblasts to support islet implantation and survival in mice. This method lengthened the survival of islet allografts 4-fold by enhancing Treg infiltration into the graft itself and the draining lymph nodes [297]. Importantly, insulin staining determined that these islets maintained their functionality.…”
Section: Transplantation the Ultimate Goal In Organ Transplantationmentioning
confidence: 99%
“…We found that they functionally recovered the remaining islet beta cells and successfully reversed hyperglycemia in a prominently high percentage of NOD mouse recipients due to regulating several possible immunological contributing factors of T1D. Although the previous studies from our group have identified the suppressive effects of IDO on alloimmunity in islet transplantation (Jalili et al, ; Poormasjedi‐Meibod et al, ; Hosseini‐Tabatabaei et al, ), this is the first study to show the role of optimized IDO‐expressing fibroblasts in the regulation of autoimmune diabetes and the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 57%
“…Mesenchymal stem cells expressing IDO have been linked to increased renal graft survival. Mice experiments showed that islets equipped with IDO‐expressing fibroblasts extend graft survival . This example nicely illustrates the interplay between these different immunoprotective factors.…”
Section: Ctla‐4 Pd‐l1 and Idomentioning
confidence: 64%